Protective Effect of Resveratrol against Glioblastoma: A Review - Ashrafizadeh, Milad; Mohammadinejad, Reza; Farkhondeh, Tahereh; Samarghandian, Saeed (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: One of the most common tumors of the central nervous system is Glioblastoma (GBM). Objective: There is not still an appropriate cure for this malignant tumor. Plant-derived natural products have demonstrated great potential in cancer therapy, and Resveratrol (Res) is among them. Therefore, the current study focused on the protective effect of resveratrol against glioblastoma and its underlying mechanism. Methods: PubMed, Medline, Scopus, Web of Science, and Google Scholar were searched by using the following keywords: Resveratrol, Glioblastoma, Brain tumor, Cancer therapy, Medicinal herbs to July 2020. Results: Res is a non-flavonoid polyphenol responsible for the protection of plants against pathogen attacks. Res has multiple pharmacological effects, including antioxidant, anti-inflammatory, anti-diabetic, and anti-tumor. Res is capable of penetration into the blood-brain barrier, making it suitable for brain tumor therapy. Besides, Res targets various molecular signaling pathways in cancer therapy. Conclusion: In the present review, it was found that Res administration is beneficial in GBM therapy by inhibition of proliferation, viability, and migration via modulation of molecular pathways.
Keywords: Resveratrol